2021
DOI: 10.1186/s13148-021-01152-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylome profiling reveals epigenetic regulation of lipoprotein-associated phospholipase A2 in human vulnerable atherosclerotic plaque

Abstract: Background Atherosclerotic plaque vulnerability is a key feature of atheroprogression and precipitating acute cardiovascular events. Although the pivotal role of epigenetic regulation in atherosclerotic plaque destabilization is being recognized, the DNA methylation profile and its potential role in driving the progression and destabilization of atherosclerotic cardiovascular disease remains largely unknown. We conducted a genome-wide analysis to identify differentially methylated genes in vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…A bioinformatic study reported an imprinted gene PLA2G7, which encoded lipoprotein-associated phospholipase A2 (Lp-PLA2). The hypomethylation of PLA2G7 increased expression upon inflammation in AS, indicating the effects of DNA methylation modification on atheroprogression and destabilization via inflammatory processes ( Li et al, 2021 ). SMCs migrate from the media to the intima and form the AS plaques.…”
Section: Discussionmentioning
confidence: 99%
“…A bioinformatic study reported an imprinted gene PLA2G7, which encoded lipoprotein-associated phospholipase A2 (Lp-PLA2). The hypomethylation of PLA2G7 increased expression upon inflammation in AS, indicating the effects of DNA methylation modification on atheroprogression and destabilization via inflammatory processes ( Li et al, 2021 ). SMCs migrate from the media to the intima and form the AS plaques.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a large EWAS analysis with > 6400 individuals also did not identify any genome-wide significant associations between CIMT and blood cell-derived methylation levels at any CpG site except for cg05575921 at the well-known smoking-associated AHRR locus [ 22 ]. By comparison, epigenetic analyses with tissue obtained from atherosclerotic and normal carotid, aortic, mammary, or femoral artery samples have identified thousands of associations with atherosclerosis [ 20 22 , 28 30 ]. Interestingly, several studies observed hypomethylation of CpG sites in atherosclerotic tissue compared to normal arteries and upregulation of multiple pathways that could potentially be causal drivers of plaque development [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, epigenetic analyses with tissue obtained from atherosclerotic and normal carotid, aortic, mammary, or femoral artery samples have identified thousands of associations with atherosclerosis [ 20 22 , 28 30 ]. Interestingly, several studies observed hypomethylation of CpG sites in atherosclerotic tissue compared to normal arteries and upregulation of multiple pathways that could potentially be causal drivers of plaque development [ 28 , 30 ]. These findings, taken together with our data, suggest that circulating leukocytes may not be an appropriate surrogate tissue in which to associate methylation modifications with vascular wall phenotypes, even in response to HT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, promoter methylation changes occurring at AIRE1 and ALOX12 genes have been implicated as potential epigenetic alterations in the etiology of atherosclerotic plaques [ 122 ]. Importantly, large genome-wide analyses have revealed the predominance of extensive hypomethylation in atherosclerotic plaques which correlates with the expression of several genes implicated in atherogenesis such as RTL1, CDKN2B, and PLA2G7 [ 123 , 124 ]. Finally, from a clinical perspective, differentially methylated levels of BRCA1 and CRISP2 regions have been associated with subclinical atherosclerosis measures such as the coronary calcium score and carotid IMT in individuals with subclinical cardiovascular disease [ 125 ].…”
Section: Methodsmentioning
confidence: 99%